Prescription and indication for oral nutritional supplements in a Swiss university hospital: a prospective survey - Julie Mareschal; Jean Altwegg; Dimitri Berthet; Marinette Chikhi; Pierre Chopard; Séverine Graf; Christian Sierro; Claude Pichard; Laurence Genton (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY